1979
DOI: 10.1063/1.326085
|View full text |Cite
|
Sign up to set email alerts
|

Saturation of Zn2SiO4 : Mn luminescence under intense vuv excitation

Abstract: Output luminescence of Zn2SiO4 : Mn phosphor saturates under intense vacuum ultraviolet radiation having a relatively high excitation duty ratio. The saturation is attributed to the depletion of activators at the ground level. This depletion originates from the long decay time constant of the phosphor. The saturation mechanism is explained analytically using a simple model, and the conditions for efficient phosphor excitation are derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 1 publication
3
23
1
Order By: Relevance
“…Thermal effects are found to be negligible by analyzing the Mn 2+ emission green shift and intensity versus temperature; the 150 1C efficiency of HALO is 490% of the room temperature value. Given the literature on the saturation of Mn 2+ phosphors whose main cause is the slow Mn 2+ emission (t$11.3 ms in HALO) [12][13][14][15][16][17], it is reasonable to assign the Mn 2+ quenching of HALO in these pcLEDs to saturation. However, standard models cannot explain the Eu 2+ quenching due to the fast radiative decay time of Eu 2+ (t$580 ns for Ca 5 (PO 4 ) 3 Cl:Eu 2+ ), and experiments with Eu 2+ phosphors in similar pcLEDs show virtually no quenching with variations in the LED excitation duty cycle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal effects are found to be negligible by analyzing the Mn 2+ emission green shift and intensity versus temperature; the 150 1C efficiency of HALO is 490% of the room temperature value. Given the literature on the saturation of Mn 2+ phosphors whose main cause is the slow Mn 2+ emission (t$11.3 ms in HALO) [12][13][14][15][16][17], it is reasonable to assign the Mn 2+ quenching of HALO in these pcLEDs to saturation. However, standard models cannot explain the Eu 2+ quenching due to the fast radiative decay time of Eu 2+ (t$580 ns for Ca 5 (PO 4 ) 3 Cl:Eu 2+ ), and experiments with Eu 2+ phosphors in similar pcLEDs show virtually no quenching with variations in the LED excitation duty cycle.…”
Section: Resultsmentioning
confidence: 99%
“…8). Taking this similarity into account, we take the route of using rate equations to analyze both Eu 2+ and Mn 2+ emission quenching with the addition of ground state depletion [12,16,17] due to the long Mn 2+ lifetime and relatively high violet LED fluxes (89 s À1 ), and k rate constant for ET between excited Mn 2+ ions [13,17,20]. There are two main assumptions that we have in using these rate equations.…”
Section: Article In Pressmentioning
confidence: 99%
“…Three plausible mechanisms for intrinsic saturation phenomena in inorganic phosphors are proposed in the literature: activator ground-state depletion [26][27][28], excited-state interaction [28,29] and quenching due to laser-induced temperature rise [28]. Each is explored below, in the context of this particular phosphor and in view of the various results presented in this paper.…”
Section: Investigating the Saturation Of The Phosphorescence Emissionmentioning
confidence: 99%
“…In addition, the luminance of developed phosphors should be enhanced again because of their improved saturation properties. It was reported that the lightemitting efficiency of phosphors decreased under intense excitation due to a luminescence saturation phenomenon [7,21]. Specially, the efficiency of Zn 2 SiO 4 :Mn 2+ decreased to $70% of its maximum efficiency (Table 1).…”
Section: Measurements Of Luminescence Propertiesmentioning
confidence: 93%